Implementation of Religious Moderation Values in Shaping the Social Character of Elementary School Students - Vina Tamarin; Nur Hidayat (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to understand the explanation regarding the implementation of religious moderation values in shaping the social character of elementary school students. The study utilizes a descriptive qualitative approach with data collection techniques conducted through interviews with teachers from Madrasah Ibtidaiyah classes in Bandung City. The data analysis employed includes data condensation, data presentation, and drawing conclusions. The results of this research indicate that the implementation of religious moderation values in shaping students' social character can be achieved at the elementary school level through habitual practices embedded in the learning materials. Explanation regarding the diversity present in the environment should be taught to students to enable them to practice tolerance as a form of character development.